Understanding healthcare professionals’ responses to patient complaints in secondary and tertiary care in the UK: a systematic review and behavioural analysis using the Theoretical Domains Framework - Antonopoulou, Vivi; Meyer, Carly; Chadwick, Paul; Gibson, Beckie; Sniehotta, Falko F.; Vlaev, Ivo; Vassova, Anna; Goffe, Louis; Lorencatto, Fabiana; McKinlay, Alison; Chater, Angel Marie (Health research policy and systems, 2024)
The path of a complaint and patient satisfaction with complaint resolution is often dependent on the responses of healthcare professionals (HCPs). It is therefore important to understand the influences shaping HCP behaviour. This systematic review aimed to (1) identify the key actors, behaviours and factors influencing HCPs’ responses to complaints, and (2) apply behavioural science frameworks to classify these influences and provide recommendations for more effective complaints handling behaviours.
Online veröffentlicht: 1. Oktober 2024
Gesehen am 15.04.2025